Adaptive STATCOM Control for a Multi-machine Power System - Rahim, A.H.M.A. (2020)
Synchronous static compensator (STATCOM) can be used to improve the dynamic performance of a power system. This article presents an online adaptive pole-shift method for stabilization of a multi-machine power system. Considering the speed deviation of the generator to which the STATCOM is connected as the output and the magnitude of the converter voltage as the input, an adaptive linear plant model is estimated. The stabilizing control is derived from a variable pole-shift strategy which moves the poles of the identified model to the center of unit circle in z-domain. The controller performance has been tested for various disturbances from a number of simulation studies on a multi-machine power system. It was observed that the adaptive algorithm converges very quickly and also provides robust damping profiles to the under damped power system. Index Terms — Adaptive control, Variable pole-shift control, Power system damping control.